Evaluation of Anthelmintic Properties of Kalanchoe petitiana Essential Oil and Extracts on Caenorhabditis elegans - Dagnaw, Abera Dessie; Mitku, Melese Legesse; Bizuneh, Gizachew Kassahun (Iranian Journal of Pharmaceutical Sciences, 2025)
This study explores the chemical composition and anthelmintic activity of essential oils and extracts derived from the roots of Kalanchoe petitiana (Crassulaceae), a plant traditionally used in Ethiopian and Eritrean medicine. Essential oils were extracted through hydrodistillation and analyzed using gas chromatography-mass spectrometry (GC-MS), revealing 30 volatile compounds, with trans-myrtanol (43.23%), 1-octen-3-ol (5.43%), and bisabolene (6.02%) as the major components. The anthelmintic efficacy of the extracts and essential oil was evaluated in vitro against Caenorhabditis elegans nematodes. The methanol root extract exhibited significant nematocidal activity, achieving 91.5% mortality at a concentration of 10 mg/mL, while the chloroform root fraction demonstrated 61.7% efficacy at 2 mg/mL. The essential oil showed a potent effect with a 92.4% nematocidal rate at 60 μg/mL, closely comparable to the reference drug ivermectin (97.6% at 10 μg/mL). These results suggest that K. petitiana possesses substantial anthelmintic potential, likely due to its rich terpene content, particularly trans-myrtanol. This study provides the first report of trans-myrtanol identification from Kalanchoe species and supports using K. petitiana as a natural alternative for managing helminthic infections. Further research is recommended to isolate and characterize the active compounds and evaluate their vivo efficacy and safety.